2021
DOI: 10.3389/fmolb.2021.645845
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Defined Risk Signature of the Ferroptosis-Related Genes for Predicting the Prognosis of Ovarian Cancer

Abstract: Ferroptosis is an iron-dependent, regulated form of cell death, and the process is complex, consisting of a variety of metabolites and biological molecules. Ovarian cancer (OC) is a highly malignant gynecologic tumor with a poor survival rate. However, the predictive role of ferroptosis-related genes in ovarian cancer prognosis remains unknown. In this study, we demonstrated that the 57 ferroptosis-related genes were expressed differently between ovarian cancer and normal ovarian tissue, and based on these gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
(25 reference statements)
0
31
1
Order By: Relevance
“…Previous reports indicated that increased abundance of NK cells can bring better immunotherapy efficacy [ 52 ], further suggesting the low-risk GC patients have a better response to immunotherapy. In fact, the relationship between ferroptosis and cancer immunotherapy has been reported in 2019 [ 50 , 53 ], showing the sensitivity of tumor cells to ferroptosis is parallel to immune functions, which may be the reasonable explanation for the better response to immunotherapy in low-risk patients. But the exact mechanisms of how these 10 ferroptosis-related genes interact to affect tumorigenesis and immune process are still unclear and further studies are demanded.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that increased abundance of NK cells can bring better immunotherapy efficacy [ 52 ], further suggesting the low-risk GC patients have a better response to immunotherapy. In fact, the relationship between ferroptosis and cancer immunotherapy has been reported in 2019 [ 50 , 53 ], showing the sensitivity of tumor cells to ferroptosis is parallel to immune functions, which may be the reasonable explanation for the better response to immunotherapy in low-risk patients. But the exact mechanisms of how these 10 ferroptosis-related genes interact to affect tumorigenesis and immune process are still unclear and further studies are demanded.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a unique form of regulated cell death associated with iron metabolism, which is different from apoptosis, necrosis, and autophagy (3). Although the detailed mechanism underlying the role of ferroptosis in tumors is still unclear, several studies have reported that ferroptosis is involved in various cancers, including breast cancer (4)(5)(6), pancreatic cancer (7), ovarian cancer (8), and HCC (9)(10)(11)(12). Compared to normal nontumor cells, cancer cells have a higher level of iron, which indicates the potential of ferroptosis inducers in new antitumor strategies (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Then we screened out hub genes in a co-expression network and further identified survival-associated genes among them by using GEPIA (Gene Expression Profiling Interactive Analysis) ( Tang et al, 2017 ). Considering that Ridge, Elastic Net, and Lasso (least absolute shrinkage and selection operator) methods were widely used data mining methods especially for regression model construction ( Ye et al, 2021 ), based on the survival-associated genes, all the three methods were included for constructing multiple-gene signatures by using the data from TCGA database. Two prognostic models were constructed, which could significantly predict the OS (overall survival) of patients with ACC.…”
Section: Introductionmentioning
confidence: 99%